Eyeball (Office) urodynamics: is there value to predict hidden (Occult) stress urinary incontinence with sims speculum reduction in patients with pelvic organ prolapse? – a retrospective descriptive study - Grootboom, Nombongo Monica (Stellenbosch : Stellenbosch University, 2019)
Thesis (MMed)--Stellenbosch University, 2019.